Attitudes to Alzheimer's disease testing of Australian general practice patients: a cross‐sectional questionnaire‐based study. (10th August 2015) - Magin, Parker; Juratowitch, Laura; Dunbabin, Janet; McElduff, Patrick; Goode, Susan; Tapley, Amanda; Pond, Dimity
Abstract : Objective: In view of proposed screening for presymptomatic Alzheimer's disease (AD) with advanced imaging, and blood and cerebral spinal fluid analysis, we aimed to establish levels, and associations, of acceptance of AD testing modalities by general practice patients. Methods: A cross‐sectional questionnaire‐based study of consecutive patients (aged 50 years and over) of general practices of an Australian practice‐based research network was used. The questionnaire elicited demographic data and attitudes to screening for other diseases and included the screening acceptance domain of the Perceptions Regarding Investigational Screening for Memory in Primary Care (PRISM‐PC) instrument. This assesses receptivity to modalities of testing for AD: short questionnaire, blood test, cerebral imaging, and annual physician examination. Reflecting speculation of possible future AD diagnostic methods, an item regarding testing cerebral spinal fluid was also included. Associations of PRISM‐PC scores were analyzed with multiple linear regression. Results: Of 489 participants (response rate 87%), 66.2% would like to know if they had AD. Participants were more accepting of testing modalities that were noninvasive or familiar (questionnaire, physician's examination, and blood test) as opposed to cerebral imaging or lumbar puncture. Attitudes to AD testing are influenced by a positive attitude to disease screening in general. Patients with a self‐perceived higher risk of AD were less accepting of testing, as were participants with an educational level of junior high school (10 school years) or less. Conclusions: This study demonstrates that a majority of patients would like to know if they have AD. Acceptability of testing modalities, however, varies. Noninvasive, familiar methods are more acceptable. Copyright © 2015 John Wiley & Sons, Ltd.